The PERANAN ULASAN PRODUK, KEMUDAHAN, KEPERCAYAAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKOPEDIA (OZZIE MOTOR) - Nursalin, Kezia Kurniawati; Tjiptodjojo, Kartika Imasari; Kristiawan, Allen; Hidayatullah , Hasan (FEB Universitas Sam Ratulangi Manado, 2024)
The increasing use of e-commerce to carry out online buying and selling transactions has an impact on business activities in Indonesia. DKI Jakarta, West Java and the Special Region of Yogyakarta are the three provinces with the largest business activities using e-commerce in Indonesia (E Commerce Statistics; 2021). Research by Zheng & Jin (2016) shows that seller reputation in e-commerce influences consumer decisions in choosing products. To decide to buy online, there are usually many considerations such as: product reviews, convenience, trustworthiness and product price. This research aims to determine the role of product reviews, convenience, trust and price on purchasing decisions for one of the automotive industry players, namely Ozzie Motor, which markets digitally using Tokopedia e-commerce. Key Words: Product Reviews, Convenience, Trust, Price, Purchase Decisions.